PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH SISWA PADA PEMBELAJARAN IPAS DI KELAS V SD - Junedi, Kasim; Lili Kasmini; Haris Munandar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is based on the low problem-solving ability of studens in learning Natural and Social Science IPAS class V State Elementary School 61 Banda Aceh. Based on the results of initial observation and interviews with the class teacher, it is known that learning is still centered on the teacher so that students are less active and have difficulty in understanding and solving problems related to learning materials, especially in the material seeing because of light. This research aims to describe the implementation of the PBL problem Based Learning model and to find out the improvement of students' problem-solving skills in IPAS learning. This research uses a qualitative approach with a descriptive method. The research subjects consist of a class V teacher and a class V student with a total of 18 students at SD Negeri 61 Banda Aceh. Data collection techniques are carried out through observation, interviews, documentation, and tests as support.   The research results show that the implementation of the PBL model is able to improve students' creativity in the learning process as well as train students' problem-solving skills, which has increased students' ability to understand problems, discuss solutions, conduct experiments, and associate materials with daily life. Thus, the Problem Based Learning model can be one of the effective learning alternatives to improve students' problem-solving skills in IPAS learning in elementary school.